2020
DOI: 10.3390/atmos11020127
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on Cooling Period Thermal Comfort Assessment in Modern Open Office Landscape in Estonia

Abstract: Local thermal comfort and draught rate has been studied widely. There has been more meaningful research performed in controlled boundary condition situations than in actual work environments involving occupants. Thermal comfort conditions in office buildings in Estonia have been barely investigated in the past. In this paper, the results of thermal comfort and draught rate assessment in five office buildings in Tallinn are presented and discussed. Studied office landscapes vary in heating, ventilation and cool… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Comparing the PETs among the runway and irrigated grass, the daytime (08:00-20:00) average PETs were 39.3 • C and 33.8 • C. Irrigating the grass can improve HTC in the daytime. Nevertheless, the magnitude of nighttime PET variability was found to be smaller than daytime PET, with an average range of 2.4 • C and an average daily variability of 5.5 • C. Water-sensitive urban design features can provide positive benefits for improving HTC and thermal comfort assessment (TCA) through reductions in air temperature and surface temperature, but important enhancements can also be obtained through amplifying the effect of shade and ventilation [13,37,38]. Other studies explored the role of street trees in cooling the urban microclimate and improving HTC, and noted that street tree canopies increases the cooling effect as street canyon geometry shallows and broadens [38,39].…”
Section: Land Surface Temperature Air Temperature and Relative Humiditymentioning
confidence: 99%
“…Comparing the PETs among the runway and irrigated grass, the daytime (08:00-20:00) average PETs were 39.3 • C and 33.8 • C. Irrigating the grass can improve HTC in the daytime. Nevertheless, the magnitude of nighttime PET variability was found to be smaller than daytime PET, with an average range of 2.4 • C and an average daily variability of 5.5 • C. Water-sensitive urban design features can provide positive benefits for improving HTC and thermal comfort assessment (TCA) through reductions in air temperature and surface temperature, but important enhancements can also be obtained through amplifying the effect of shade and ventilation [13,37,38]. Other studies explored the role of street trees in cooling the urban microclimate and improving HTC, and noted that street tree canopies increases the cooling effect as street canyon geometry shallows and broadens [38,39].…”
Section: Land Surface Temperature Air Temperature and Relative Humiditymentioning
confidence: 99%
“…In a study [2] conducted in Tallinn, thermal comfort (TC) and draught rate (DR) assessment was carried out in both heating and cooling period conditions. The office buildings were equipped with different HVAC solutions.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that DR was below 10% in heating and transient period measurements, but the risk of draught was assessed for the intensive cooling mode. In a later paper [16], it was concluded that avoiding fan coil units for cooling would not guarantee better thermal comfort for the occupants without draught complaints.…”
Section: Introductionmentioning
confidence: 99%
“…Kiil et al [16] also provided criticism towards the existing standards in terms of DR: they found out that the standards do not specify how to select relevant conditions and locations for measurement of DR. The study has also concluded that the standards do not provide questionnaires for the assessment of occupant dissatisfaction, which are detailed enough.…”
Section: Introductionmentioning
confidence: 99%